1985
DOI: 10.1515/botm.1985.28.12.521
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Agar from Gracilaria Spp (Rhodophyta) Collected in the People's Republic of China

Abstract: The structure of agars obtained from Gracilaria verrucosa, G. tenuistipitata, G. blodgettii, and G. eucheumoides collected in the People's Republic of China was determined. The agars consisted of charged agarose molecules that were eluted from DEAE-Sephadex A 50 with 0.5 Μ and 1.0 Μ Nad. The yield of agar from DEAE-Sephadex was increased to 80% after a treatment with 6.0 Μ urea, with the recovery of agarose molecules having a low charge density. Analysis by 13 C MNR spectroscopy showed L-gaIactose-6-sulfate as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0
2

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 23 publications
5
10
0
2
Order By: Relevance
“…Hoyle (1978) did not find differences in the yield or in the gel strength of the agar from male, female and tetrasporic plants of Gracilaria bursapastoris (Gmelin) Silva and G. coronopifolia J. Agardh (names as in the original paper). Similar findings were reported by Yao et al (1984) and Minghou et al (1985) for tetrasporic vs cystocarpic plants of G. verrucosa (Hudson) Papenfuss, and by Durairatnam and Nascimento (1985) for Gelidiopsis sjoestedtii Kylin. Neither Yao et al (1984) nor Minghou et al (1985) reported major differences in 3,6-anhydrogalactose and sulfate contents of the agar extracted from reproductive phases of Gracilaria species.…”
Section: Introductionsupporting
confidence: 86%
“…Hoyle (1978) did not find differences in the yield or in the gel strength of the agar from male, female and tetrasporic plants of Gracilaria bursapastoris (Gmelin) Silva and G. coronopifolia J. Agardh (names as in the original paper). Similar findings were reported by Yao et al (1984) and Minghou et al (1985) for tetrasporic vs cystocarpic plants of G. verrucosa (Hudson) Papenfuss, and by Durairatnam and Nascimento (1985) for Gelidiopsis sjoestedtii Kylin. Neither Yao et al (1984) nor Minghou et al (1985) reported major differences in 3,6-anhydrogalactose and sulfate contents of the agar extracted from reproductive phases of Gracilaria species.…”
Section: Introductionsupporting
confidence: 86%
“…Agar is known to be a mixture of molecules having a structure of the idealized agarose molecules and partially modified agarose substituted by sulfate, methoxyl and 4,6-0-(1-carboxyethylidene)-D-galactose at various positions (Araki, 1966;. The chemical heterogeneity of agar has been determined using anion exchange chromatography, sequential solvent extraction, 3 C -NMR and IR spectrophotometry (Minghou et al, 1985(Minghou et al, , 1988Yang & Liu, 1988;Truong et al, 1988;Lahaye et al, 1986;.…”
Section: Introductionmentioning
confidence: 99%
“…All extracts were run at 77 'C, at which temperature they still would have been in the gel state ; however, the sharpness of the signals is comparable with those obtained at 90 ° C (Nicholaisen et al, 1980b) . The gel state spectrum of agarDB shows one minor peak at 58 .9 ppm due to the methyl carbon on a 6-0-methylated galactose residue, and another two at 71 .6 ppm and 73 .4 ppm, due to G-6 and G-5 carbons, respectively, of the methylated residue (Minghou et al, 1985). The peak at 69.2 ppm due to G-4 carbon of the same residue also was discernible .…”
Section: Gel State Spectra -Extractsmentioning
confidence: 90%
“…The peak at 69.2 ppm due to G-4 carbon of the same residue also was discernible . In the Sigma agarose spectrum, a slight peak at 59 .0 ppm for methoxyl carbon was discernible, as well as two very minor peaks at 78 .7 and 78 .3 ppm, possibly due to carbons of anhydrogalactose residues methylated in the 2 position (Minghou et al ., 1985) . The agar extracted from E112 (Pterocladia capillacea), I although crude, has a spectrum that shows virtually no substitution .…”
Section: Gel State Spectra -Extractsmentioning
confidence: 99%